Effective PEGylation of gold nanorods. Issue 13 (15th March 2016) - Schulz, F.; Friedrich, W.; Hoppe, K.; Vossmeyer, T.; Weller, H.; Lange, H.
Abstract : Gold nanorods with high PEG grafting densities are synthesized with a tailored PEG ligand that favors ligand exchange and provides very high colloidal and chemical stabilization. The ligand exchange of the gold nanorods is studied utilizing oxidative etching with cyanide to prove that it is faster, less ligand consuming and more reproducible when assisted by chloroform extraction. Abstract : Standard procedures to coat gold nanorods (AuNR) with poly(ethylene glycol) (PEG)-based ligands are not reliable and high PEG-grafting densities are not achieved. In this work, the ligand exchange of AuNR with PEGMUA, a tailored PEG-ligand bearing a C10 alkylene spacer, is studied. PEGMUA provides AuNR with very high stability against oxidative etching with cyanide. This etching reaction is utilized to study the ligand exchange in detail. Ligand exchange is faster, less ligand consuming and more reproducible with assisting chloroform extraction. Compared to PEG ligands commonly used, PEGMUA provides much higher colloidal and chemical stability. Further analyses based on NMR-, IR- and UV/Vis-spectroscopy reveal that significantly higher PEG-grafting densities, up to ∼3 nm −2, are obtained with PEGMUA. This demonstrates how the molecular structure of the PEG ligand can be used to dramatically improve the ligand exchange and to synthesize PEGylated AuNR with high chemical and colloidal stability and high PEG grafting densities. Such AuNR are especially interesting for applications in nanomedicine.